THE ROLE OF GROUP DISCUSSION IN IMPROVING STUDENTS’ VOCABULARY AT SMA PERSADA BANDAR LAMPUNG - Dian Cahyaning Pertiwi; Helta Anggia (Universitas Bandar Lampung, 2017)
This research aimed to know how the role group discussion in improving students’ vocabulary mastery at SMA Persada Bandar Lampung. This research was qualitative method which used triangulation method – observation, questionnaire, and interview. The researcher also gave activity for students to strengthen the result of triangulation data. This subject of research was consisted of 24 students of X.2 at SMA Persada Bandar Lampung.The result showed that the highest percentage 62.5% strongly agree was about ‘active participant’ as indicator which made improvement for students’ vocabulary. Students felt active while they were having group discussion. On the other hand, the result also showed the students’ social skill development in during group discussion. Some students said they could share their opinion with their friends. It meant that the role of group discussion could give influence to students’ vocabulary in learning English at SMA Persada Bandar Lampung. In conclusion, the role of group discussion was very helpful in learning.